Рівень фізичної підготовленості студентів = Level of physical fitness students - Igor Pelech; Igor Grygus (Kazimierz Wielki University, 2016)
Pelech I. V., Grygus I. M. Рівень фізичної підготовленості студентів = Level of physical fitness students. Journal of Education, Health and Sport. 2016;6(2):87-98. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.46057 http://ojs.ukw.edu.pl/index.php/johs/article/view/3381 https://pbn.nauka.gov.pl/works/714160   The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 01.01.2016. Revised 12.01.2016. Accepted: 31.01.2016.     Рівень фізичної підготовленості студентів Level of physical fitness STUDENTS   І.В. Пелех1, І.М. Григус2 I.V. Pelech1, I.M. Grygus2   Новоград-Волинський промислово-економічний технікум1, Національний університет водного господарства та природокористування2   Novograd-Volynsky industrial and economic college1, National University of Water Management and Nature Resources Use2   Abstract   This article is devoted to the study of physical fitness of students. The current state of the problem, scientists working on this issues. The level of physical fitness of 60 students in the fourth year of training at the beginning of the school year. Given the lack of physical fitness of students planned to develop approaches to physical education classes students would be based on an integrated use of traditional means of physical education and modern species without additional financial cost and volume of academic hours.   Keywords: students, physical education, testing, physical training.   Анотація   Стаття присвячена вивченню фізичної підготовленості студентів. Проаналізовано сучасний стан проблеми, роботи науковців за даною проблематикою. Визначено рівень фізичної підготовленості 60 студентів четвертого року навчання на початку навчального року. Враховуючи недостатню фізичну підготовленість студентів, заплановано розробити підходи до організації занять з фізичного виховання студентів, які б ґрунтувалися на комплексному застосуванні традиційних засобів фізичного виховання і сучасних видів без додаткових фінансових витрат та обсягу академічних годин.   Ключові слова: студенти, фізичне виховання, тестування, фізична підготовленість.